2021
DOI: 10.1590/s1980-220x2020024903727
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of patients in hospital units: impacts on nursing workload

Abstract: Objective: To measure the average time spent by the nursing team in transferring patients; to compare the activities observed during the performance of this intervention with those described by the Nursing Interventions Classification and to investigate the intensity of its influence on the workload. Method: Observational study using timekeeping software conducted in two hospitals in the northwest region of the State of São Paulo. 200 patient transfers were monitored by the team using two validated instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 17 publications
0
12
0
9
Order By: Relevance
“…The results suggest that 38.1% of patients do not comply with safe transport [ 23 ]. In the survey data of in-hospital transport of critically ill patients, it was found that the incidence of side effects related to the patient's condition was about 31%, including the circulatory system, respiratory system, digestive system, and central nervous system [ 24 ]. In other scholars' studies, respiratory and cardiac arrest may occur in patients with severe craniocerebral injury, cerebral hemorrhage, cardiac injury, pericardial tamponade, myocardial infarction, heart failure, and respiratory failure [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that 38.1% of patients do not comply with safe transport [ 23 ]. In the survey data of in-hospital transport of critically ill patients, it was found that the incidence of side effects related to the patient's condition was about 31%, including the circulatory system, respiratory system, digestive system, and central nervous system [ 24 ]. In other scholars' studies, respiratory and cardiac arrest may occur in patients with severe craniocerebral injury, cerebral hemorrhage, cardiac injury, pericardial tamponade, myocardial infarction, heart failure, and respiratory failure [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Trovó et al [ 5 ] studied a patient sample ( n = 200) transferred between units under intervention 7890 Transport: between facilities. The NIC establishes that the average time needed to carry out this intervention is 16–30 min.…”
Section: Resultsmentioning
confidence: 99%
“…The only experience that has been analysed to examine the intensity of its influence on nurses’ workloads corresponds to transfers of patients between facilities [ 5 ]. Although the results were lower than the averages established in the NIC, the authors considered that, during the transfer of the patients, the nurses did not record other activities involved in continuity of care or the documentation required for the administrative process of the patients’ transfers, which would increase workloads by up to 29%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, viabiliza o planejamento do cuidado diário direto, contribuindo com a estimativa e gestão de custos. Em contraponto, existem atividades que demandam tempo de enfermagem e que ultrapassam a sensibilidade da avaliação dos SCP; logo, merecem ser consideradas no processo de planejamento da força de trabalho, ainda que isso não seja verificado na prática (9) .…”
Section: Introductionunclassified